AB1350-HPR SOCIOECONOMIC BURDEN OF NON-ATTENDANCE IN RHEUMATOLOGY CONSULTATION. (2nd June 2020) - Rodrigues, J.; Faria, D.; Silva, J.; Azevedo, S.; Guimarães, F.; Almeida, D.; Afonso, C.; Alcino, S.; Peixoto, D.; Teixeira, F.; Tavares-Costa, J.
Abstract : Background: Outpatient non-attendance refers to the phenomenon of patients who have a medical appointment but do not show up at the specified date, time, and location without giving previous notice. 1 In addition to affecting the efficiency and thereby increasing the healthcare total costs, nonattendance might also delay access to care for users on waiting lists. 1 Nonattendance at health appointments is costly to services, and can risk patient health. 2 There is very little data on the nonattendance prevalence and impact in Portugal. This knowledge might be fundamental to improve effectiveness of outpatient care in Portugal. Objectives: 1) describe patient's non-attendance rate; 2) assess and characterize the sociodemographic and clinical characteristics among non-attending patients; 3) estimate the economic burden of non-attendance. Methods: Retrospective, cross-sectional and analytical study. We reviewed a one-month Rheumatology consultation period regarding performed medical consultations and non-attended consultations without previous notification from patients. Direct economic costs of non-attended appointments were calculated based on the "Amending Agreement to the ULSAM, EPE Program Agreement". Results: 982 consultations within January 2018 were included. Appointments episodes for therapeutic prescription, medical reports or programmed admissions were excluded. Fifty-seven (5.8%) of scheduled outpatient appointments were non-attended. Subsequent consultations represented 85.2% of attended appointments and 80.7% of non-attended appointments. Female gender was the most prevalent in both groups – 620 (67.0%) among attended consultations and 37 (65.0%) among non-attended consultations. Mean age was 57±15 years in the first group and 54±16 years in the second one. Among attended appointments, mean education level was 8±5 years versus 9±6 years among non-attended appointments. There were no differences between both groups in gender, age, education level, diagnosis, disease duration and activity or appointment type (first or subsequent consultation). A cost of 2, 438 euros was estimated regarding non-attended appointments for this period, what could represent a burden of more than 29, 000 euros yearly, in direct costs, only. Conclusion: Non-attendance at scheduled appointments in public hospitals seems to be influenced by other factors besides gender, age and education level. The burden of non-attended appointments is undeniable. In addition to the costs estimated in this study, further indirect costs such as poorer patients outcomes, impaired access to medical care and hospital penalties should be taken into account. Implementation of awareness strategies aiming the optimization and effectiveness of healthcare system are required. References: [1]Blæhr EE, Kristensen T, Væggemose U, Søgaard R. The effect of fines on nonattendance in public hospital outpatient clinics: study protocol for a randomized controlled trial. Trials . 2016;17(1):288. doi:10.1186/s13063-016-1420-3 [2]Akter S. A qualitative study of staff perspectives of patient non-attendance in a regional primary healthcare setting. Australas Med J . 2014;7(5):218-226. doi:10.4066/AMJ.2014.2056 Disclosure of Interests: None declared